Targeting Proteasomes in Cancer and Infectious Disease: A Parallel Strategy to Treat Malignancies and Microbes - Ignatz-Hoover, James J.; Murphy, Elena V.; Driscoll, James J. (Frontiers in Cellular and Infection Microbiology, 2022)
Essential core pathways of cellular biology are preserved throughout evolution, highlighting the importance of these pathways for both bacteria and human cancer cells alike. Cell viability requires a proper balance between protein synthesis and degradation in order to maintain integrity of the proteome. Proteasomes are highly intricate, tightly regulated multisubunit complexes that are critical to achieve protein homeostasis (proteostasis) by the selective degradation of misfolded, redundant and damaged proteins. Proteasomes function as the catalytic core of the ubiquitin-proteasome system (UPS) which regulates a myriad of essential cellular processes including cell growth, survival, differentiation, drug resistance and apoptosis. Proteasomes recognize and degrade proteins that have been tagged through the covalent attachment of one or more poly-ubiquitin chains. Deregulation of the UPS has emerged as one of the essential etiologies in many prominent diseases, including cancer. Proteasome inhibitors induce apoptosis in cancer cells, including those resistant to conventional chemotherapy, while sparing healthy cells and proteasome inhibition has emerged as an important therapeutic in the treatment of multiple myeloma. The structural arrangement and functional activity is conserved from Archae to humans to suggest that proteasomes in pathogens also represent actionable targets that can be inhibited as a feasible approach to treat infectious diseases. With growing resistance to conventional drugs, proteasome inhibition may represent a novel therapeutic strategy to eliminate Plasmodium falciparum and Mycobacteria tuberculosis. The essential role of proteasomes during all parasitic life cycle stages, synergy with frontline agents, and identification of differences between bacterial and human proteasomes support further development of proteasome inhibitors in the treatment of diseases caused by infectious agents. The proteasome represents a highly promising, actionable target to combat infectious diseases that devastate lives and livelihoods around the globe.